Exploring the remarkable effect of ursodeoxycholic acid and Allium sativum combination on MMP-9 and TIMP-1 levels in cholestatic rat’s model - Sekartaji, Anindhita Dyah; Prasetyo, Sigit Adi; Muniroh, Muflihatul (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2024)
Background: Cholestasis is a disturbance in the production or flow of bile that causes excessive accumulation of bile fluid and damage in the liver. Chronic liver damage will lead to liver fibrosis. Matrix metalloproteinase-9 (MMP-9) and tissue inhibitors of metalloprotease-1 (TIMP-1) play a critical role in liver fibrosis formation. Although ursodeoxycholic acid (UDCA) and Allium sativum extracts have long been renowned for improving liver function, their combination in alleviating liver fibrosis through the MMP-9 and TIMP-1 inhibitory pathways has yet to be studied.Objective: This study was conducted to assess the efficacy of UDCA and Allium sativum extract combination in altering MMP-9 and TIMP-1 levels, which are the main factors in the progression of liver fibrosis.Methods: We performed an experimental study with a post-test-only control group on 36 Sprague-Dawley rats, which were randomly grouped into healthy, negative, positive, and three treatment groups with UDCA (13.5 mg) and graded doses of Allium sativum extract (3.6 mg; 7.2 mg; and 14.4 mg). Cholestasis induction was done by a choledochal duct ligation, and treatment was given for 14 days. Levels of MMP-9 and TIMP-1 were analyzed after treatment.Results: Combining UDCA and Allium sativum improved the MMP-9 levels significantly in cholestatic rats, compared to administrating UDCA only (p <0.05). Combining UDCA and Allium sativum increased the TIMP-1 level (p < 0.05). Although the MMP-9 level results were under our existing hypothesis, TIMP-1 results showed surprising results. Matrix metalloproteinase-9 levels were strongly negatively correlated with TIMP-1 levels, with a r-value= 0.981.Conclusion: Combining Allium sativum and UDCA alleviates liver fibrosis progression through lowering levels of MMP-9 and increasing levels of TIMP-1.